1997
DOI: 10.1038/sj.onc.1201020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of activated Ras-induced neuronal differentiation of PC12 cells by the LIM domain of LIM-kinase 1

Abstract: LIM-kinase 1 and 2 (LIMK1 and LIMK2) are members of a novel class of protein kinases with structures composed of two LIM motifs at the N-terminus and an unusual protein kinase domain at the C-terminus. The cellular functions of the LIMK family proteins have remained unknown. In the present study, we examined e ects of LIMKs on neuronal di erentiation of PC12 pheochromocytoma cells. Transient expression analyses revealed that LIMK1, in itself, had no apparent e ect on PC12 cells, but the oncogenic Ras-induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Consistent with these observations, previous studies showed that expression of dominant-negative LIMK1 or suppression of LIMK1 expression inhibited axonal outgrowth from hippocampal pyramidal neurons (14,22). Furthermore, overexpression of the LIM domain of LIMK1, which may function as a dominant-negative form to suppress endogenous LIMK1, inhibited NGF-or Ras-induced neurite extension from PC12 cells (31,32). Together these observations suggest that LIMK1 and LIMK2 stimulates neurite extension through their cofilin-phosphorylating activity.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with these observations, previous studies showed that expression of dominant-negative LIMK1 or suppression of LIMK1 expression inhibited axonal outgrowth from hippocampal pyramidal neurons (14,22). Furthermore, overexpression of the LIM domain of LIMK1, which may function as a dominant-negative form to suppress endogenous LIMK1, inhibited NGF-or Ras-induced neurite extension from PC12 cells (31,32). Together these observations suggest that LIMK1 and LIMK2 stimulates neurite extension through their cofilin-phosphorylating activity.…”
Section: Discussionsupporting
confidence: 76%
“…The non-catalytic domain of LIMK1 has been shown to have effects on cytoskeleton reorganization independent of its kinase activity. Specific regions of the non-catalytic domain (LIM or PDZ) inhibit neurite outgrowth in differentiating PC12 cells in response to Ras, neuronal growth factor (NGF) or a ROCK inhibitor without altering endogenous LIMK1 activity (13,14). These observations suggest that the non-catalytic domain of LIMK1 is involved in regulating cellular processes though protein-protein interaction.…”
mentioning
confidence: 81%
“…On the other hand, LIMK1 inhibits neuronal differentiation in rat pheochromocytoma PC12 cells through its LIM domain and by interfering with events downstream of mitogen-activated protein kinase activation (54). In addition, the Rho-associated kinase-dependent pathway is reported to suppress nerve growth factor-induced Rac activation and the neurite outgrowth of PC12 cells (55,56).…”
Section: Discussionmentioning
confidence: 99%